Perbandingan Pelarut Etanol dan Gliserin pada Ekstrak Etanol Buah Bit (Beta vulgaris L.) terhadap Pertumbuhan Bakteri Staphylococcus aureus - Tiani Nduru; Astriani Natalia Br Ginting; Roy Indrianto Bangar (SEHATMAS: Jurnal Ilmiah Kesehatan Masyarakat, 2026)
Infectious diseases caused by Staphylococcus aureus remain a significant health concern globally, with increasing antibiotic resistance necessitating alternative antimicrobial agents. Beetroot (Beta vulgaris L.) contains bioactive compounds with potential antibacterial properties. This study investigated the antibacterial activity of beetroot ethanol extract against Staphylococcus aureus and compared the effects of ethanol and aqueous solvents in the extraction process. Beetroot simplicia was prepared and characterized according to standard protocols. Extraction was performed using 70% ethanol maceration method, yielding 20.29% extract. Phytochemical screening and thin-layer chromatography identified secondary metabolites. Antibacterial activity was evaluated using the Kirby-Bauer disc diffusion method at concentrations of 5%, 10%, and 15%, both with and without glycerin addition. Simplicia characterization met quality standards with moisture content of 0.25%. TLC analysis revealed alkaloids, flavonoids, terpenoids, steroids, saponins, and tannins. Beetroot ethanol extract demonstrated concentration-dependent antibacterial activity with inhibition zones of 8.1±0.87 mm (5%), 10.2±0.71 mm (10%), and 13.9±0.79 mm (15%). Glycerin-supplemented extracts showed comparable activity. Beetroot ethanol extract exhibits significant antibacterial activity against Staphylococcus aureus, supporting its potential as a natural antimicrobial agent for pharmaceutical applications.